Managerial Supervision in Primary Education: A Systematic Literature Review of Trends, Challenges, and Implications for Teacher Professional Development - Fitriyana; Trian Hermawan; Erliyan Eka Damayanti; Nirva Diana; Agus Paharudin (Postgraduate Program Magister Pendidikan Agama Islam, 2026)
Managerial supervision in primary education has recently evolved from a traditional administrative mechanism into a strategic driver for improving instructional quality and teacher professional development. This systematic literature review aims to synthesize empirical and conceptual research published between 2020 and 2025 to identify trends, theoretical orientations, methodological patterns, and implementation challenges in managerial supervision within primary schools. Guided by the PRISMA protocol, ten high-quality studies were selected from an initial pool of 500 publications sourced from Scopus and Google Scholar. Thematic analysis indicates a global shift toward more collaborative, reflective, and data-driven supervisory practices, supported by principals’ managerial leadership competence, systematic academic supervision, and the adoption of digital tools for classroom observation and feedback. Distributed leadership also emerged as an effective model for enhancing supervisory reach and strengthening professional learning cultures. Nonetheless, implementation barriers persist, including teacher resistance, limited data literacy, and inadequate digital infrastructure, resulting in inconsistent supervisory outcomes among schools. The review highlights the need for policies that strengthen supervisory capacity, integrate technology into supervision systems, and accommodate teachers’ career stages through adaptable supervisory frameworks. Future research is recommended to employ longitudinal and experimental designs to examine the causal impact of digital-based managerial supervision on teaching quality and student learning achievement. Supervisi manajerial di pendidikan dasar dalam beberapa tahun terakhir telah mengalami perkembangan dari mekanisme administratif tradisional menjadi penggerak strategis dalam peningkatan kualitas pembelajaran dan pengembangan profesional guru. Kajian literatur sistematis ini bertujuan untuk mensintesis penelitian empiris dan konseptual yang dipublikasikan pada rentang tahun 2020 hingga 2025 guna mengidentifikasi tren, orientasi teoretis, pola metodologis, serta tantangan implementasi supervisi manajerial di sekolah dasar. Berpedoman pada protokol PRISMA, sepuluh studi berkualitas tinggi diseleksi dari sekitar 500 publikasi awal yang bersumber dari basis data Scopus dan Google Scholar.Hasil analisis tematik menunjukkan adanya pergeseran global menuju praktik supervisi yang lebih kolaboratif, reflektif, dan berbasis data, yang didukung oleh kompetensi kepemimpinan manajerial kepala sekolah, pelaksanaan supervisi akademik yang sistematis, serta pemanfaatan perangkat digital untuk observasi kelas dan pemberian umpan balik. Kepemimpinan terdistribusi juga muncul sebagai model yang efektif dalam memperluas jangkauan supervisi dan memperkuat budaya pembelajaran profesional di sekolah. Meskipun demikian, berbagai hambatan implementasi masih ditemukan, antara lain resistensi guru, keterbatasan literasi data, serta infrastruktur digital yang belum memadai, yang pada akhirnya menyebabkan ketidakkonsistenan hasil supervisi antarsekolah. Kajian ini menegaskan pentingnya kebijakan yang berorientasi pada penguatan kapasitas supervisi, integrasi teknologi ke dalam sistem supervisi, serta penyesuaian kerangka supervisi yang adaptif terhadap tahapan karier guru. Penelitian selanjutnya direkomendasikan untuk menggunakan desain longitudinal dan eksperimental guna mengkaji dampak kausal supervisi manajerial berbasis digital terhadap kualitas pembelajaran dan capaian hasil belajar peserta didik.